PREFERRED MINERAL ORIENTATIONS RELATED TO MAGMATIC FLOW IN OPHIOLITE LAYERED GABBROS - Benn K.; Allard B. (My University, 1989)
Detailed study of Shape Preferred Orientations (SPOs) and Lattice Preferred Orientations (LPOs) of olivine, clinopyroxene, and plagioclase have been carried out for samples of compositionally layered gabbro from the lower crustal section of the Oman ophiolite. These gabbros have a strong magmatic foliation and magmatic lineation which are oblique with respect to the compositional layering. The results of SPO analysis indicate that the rock fabric is due to a laminar viscous magmatic flow within the ophiolite magma chamber. LPO fabrics correspond to SPO fabrics proving that mineral shape anisometry corresponds to anisotropic growth rates controlled by crystal structure. Magmatic flow has been induced by a deformation including an important component of non-coaxial strain, as indicated by the monoclinic symmetry of the SPO fabric. It is proposed that the monoclinic symmetry may be used to determine shear sense during magmatic flow. Due to non-coaxial deformation in the magmatic state, the magmatic foliation would tend towards parallelism with compositional layering. The obliquity between magmatic foliation and compositional layering may thus provide a field criterion for magmatic shear sense determination.